Hubungan Kecemasan Dengan Kepercayaan Diri Remaja Yang Mengalami Berat Badan Berlebihan di SMA Negeri 1 Ngimbang - Puji Rahayu; Vicentia Nazida Yulanda; Abdul Rokhman; Moh. Saifudin (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
The True, adolescent obesity is a reason for concern because to the negative effects it may have on self-esteem and mental health. Adolescents who are overweight are more likely to have low self-esteem when they enter puberty. Overweight teenagers enrolled at SMA N 1 Ngimbang were the subjects of this research, which aimed to establish a connection between anxiety and self-confidence. In this research, 47 teenagers were randomly selected using a cross-sectional analytic methodology. The self-confidence and HARS anxiety questionnaires were used to gather data, which was then analyzed using the Spearman test.According to the findings of this research, 68.1% of participants reported considerable anxiety, with 72.1% falling into the uncertain group. The Spearman test revealed a strong association between anxiety and self-confidence in overweight teenagers (p = 0.000, r (s) = 0.801). In particular, adolescent females may experience anxiety due to low self-confidence brought on by an unrealistic body image, according to the research